Lessons from project-scale reducing emissions from deforestation and forest degradation: A case study in northern Lao People’s Democratic Republic - Hiratsuka, Motoshi; Hashiguchi, Hozumi; Toda, Miki; Yamanoshita, Makino Yamada (Frontiers in Forests and Global Change, 2022)
The reducing emissions from deforestation and forest degradation (REDD+) framework has been implemented over the past decade, and has led to a restructuring of forest governance systems in host countries. In the case of Lao People’s Democratic Republic, which is promoting REDD+, activities have been implemented at project, sub-national, and national scales. Project-scale REDD+ is assumed to be compatible with small-scale forestry, and usually targets local people to enhance participatory forest management through technology transfer. Such projects were also supported by foreign governments under bilateral cooperation or by private funding. In the case of sub-national- or national-scale REDD+, the Lao People’s Democratic Republic government aims to develop a system of forest monitoring, as well as related structures required by international REDD+ entities. These activities are supported by substantial funding from multilateral organizations. Lessons learned from project-scale REDD+ in northern Lao People’s Democratic Republic showed a gap in expectations among different donors and recipients regarding how to implement REDD+, in particular how to reduce dependency on forest resources in rural areas, and how to estimate and account for greenhouse gas emissions reductions with consistent methodologies at different scales. Such differences are related to the attitudes of local people toward participation, and those of the private entities that fund projects and ground-based activities. In future REDD+ schemes, the structural network or structural social capital among project-, sub- national-, and national-scale activities should be reconsidered to enhance the continued participation of stakeholders and make use of their accumulated experience and knowledge of small-scale forestry management.